Leading From the Middle: How Principals Rely on District Guidance and Organizational Conditions in Times of Crisis - Maya Kaul; Meghan Comstock; Nicole S. Simon (SAGE Publishing, 2022)
COVID-19 has presented unprecedented challenges to schools, leaving principals to lead rapid organizational change with limited guidance or support. Drawing on interviews from a larger, national study of principals at the onset of the COVID-19 pandemic, we analyzed the experiences of 20 principals in four large, urban school districts-Boston, Denver, New York, and San Diego. We found that principals relied on both district guidance and preexisting school structures and conditions as they led through the crisis. Although no principals were satisfied with district guidance, principals responded to guidance on a spectrum-from abiding, to challenging, to subverting guidance. Principals' responses were associated with their perceptions of the internal capacities of their schools, as well as the district guidance. Our findings support an emergent typology of principals as middle managers during crisis, which sheds light on how principals act as middle managers and how districts can support their work.